Kisah Para Pencari Kerja: Studi Mengenai Tantangan Para Pencari Kerja Lulusan SMK di Kabupaten Cilacap - Rosyidah Andry AL-Fiyah; Tri Rini Widyastuti; Soetji Lestari (YASIN, 2026)
Vocational High Schools (SMK) are designed to produce vocational graduates who are ready to enter the workforce. However, in Cilacap Regency, known as an industrial area in Central Java, SMK graduates are precisely the largest contributors to open unemployment. This study aims to explore the subjective experiences of SMK graduates during their transition into the workforce, identify the barriers they face, and describe their survival strategies in coping with limited job opportunities. The research employs a descriptive qualitative method with a phenomenological approach. Primary data were obtained through in-depth interviews and observations, while secondary data were gathered from journals, references, and relevant documents. The research targets were job seekers who graduated from SMK and have been unemployed for more than one year, as well as officials from the Manpower and Industry Office of Cilacap Regency. Data analysis used the interactive analysis model by Miles and Huberman. The results indicate that SMK graduates face structural and social barriers, including a gap between the learning technology used in schools and the actual demands of the industry, low mastery of soft skills, withholding of graduation certificates due to administrative (financial) issues, the implementation of fixed-term employment contracts (PKWT), limited access to job vacancy information, and a shift in the function of friendship networks into paid job-brokerage practices that exploit personal connections ('insiders') as a means to secure employment. Facing these conditions, graduates develop various adaptive strategies, such as utilizing social media as a source of job vacancy information, independently participating in training and certification programs, and establishing micro-businesses, such as flower bouquet shops and *mendoan* (traditional fried tempeh) businesses. The findings of this study demonstrate that the transition of SMK graduates into the workforce is influenced not only by competence gaps but also by structural barriers in the labor market and shifting social relations among job seekers. This research contributes to the development of the sociology of education by showing that unemployment among SMK graduates is a multidimensional issue requiring the strengthening of competencies based on industry needs, modernization of practical facilities in schools, and soft skills development to ensure graduates align with industrial demands. Furthermore, it highlights the need for expanding access to job market information and strengthening entrepreneurship education as alternatives for the economic independence of graduates.